Casos y cosas: semanario popular (Vol. 2, No.59) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: una acción criminal del prefecto, ¡La última locura! Por esas calles, De todos y para todos, ¿Cu Cú? Correo de brujas.

ENGLISH: Includes: A criminal action of the prefect, The last madness! For those streets, Of all and for all, Cu Cú? Witches' mail.
Cases and things: popular weekly magazine (Vol. 2, No.59)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas